The association between testosterone, estradiol and their ratio and mortality among US men. (5th March 2021) - Belladelli, Federico; Del Giudice, Francesco; Kasman, Alex; Salonia, Andrea; Eisenberg, Michael L
Abstract: While studies have suggested that testosterone is associated with a man's health, the relationship with other sex steroids remains uncertain. The current study aimed to investigate the association between sex steroids (i.e. testosterone, estradiol and the testosterone:estradiol ratio) and mortality in a representative sample of 1, 109 US men. Three NHANES continuous cycles (1999–2000, 2001–2002, 2003–2004) were included in our study. Serum testosterone and estradiol levels were evaluated along with sociodemographic, lifestyle and health factors. Cox proportional hazards models were used. The adjusted risk of death for men with low testosterone levels was 1.66 (95% CI = 1.00–2.74, p = .05). The adjusted risk of death for men with abnormal estradiol levels was 0.96 (95% CI = 0.48–1.91, p = .91). The adjusted risk of death for men with low testosterone to estradiol ratio was 1.27 (95% CI = 0.82–1.97, p = .88). Relevant lifestyle and health factors significantly attenuated the associations. The adjusted risk of CVD‐related death for men with low testosterone levels was 2.43 (95% CI = 1.07–5.50, p = .03). In conclusion, a significant association between testosterone and mortality and testosterone to estradiol ratio and CVD‐related mortality was identified.